Creative practices for visual artists : time, space, process - Steinbach, Kenneth (Routledge, 2018)
"Contrary to popular belief, the practice of art isnt just a product of innate talent or artistic vision; artwork emerges from an intentionally constructed and maintained artistic practice. Developed from interviews with more than 75 mid-career artists, Creative Practices for Visual Artists examines the methods and approaches highly successful artists use to stay creatively robust for a lifetime. Offering practical strategies and concrete solutions, it also looks at the impacts of digital and social media, as well as recent changes in the educational system that can hinder the formation of a strong artistic practice. Artist and educator Kenneth Steinbach addresses key issues such as: the role of embodied research and non-objective experimentation; reframing one's approach to studio time; forms of productive conflict; the positive role of anxiety; and the importance of failure for the artist. The book will be useful to students and emerging artists, the instructors that teach them, and established artists looking to develop stronger studio habits. The companion website, www.creativepracticesbook.com, provides links to artists' websites and further information.?"--Provided by publisher